2020
DOI: 10.1017/s0007114520000082
|View full text |Cite
|
Sign up to set email alerts
|

Holly polyphenols alleviate intestinal inflammation and alter microbiota composition in lipopolysaccharide-challenged pigs

Abstract: The effect of holly polyphenols (HP) on intestinal inflammation and microbiota composition was evaluated in a piglet model of lipopolysaccharide (LPS)-induced intestinal injury. A total of twenty-four piglets were used in a 2 × 2 factorial design including diet type and LPS challenge. After 16 d of feeding with a basal diet supplemented with or without 250 mg/kg HP, pigs were challenged with LPS (100 μg/kg body weight) or an equal volume of saline for 4 h, followed by analysis of disaccharidase activities, gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 37 publications
2
21
0
Order By: Relevance
“…Many studies have reported that DON can induce inflammation in vivo and in vitro [ 9 , 11 , 30 , 38 ]. Meanwhile, a large number of studies with either porcine intestinal epithelial cell culture or experimental pig models of inflammation have convincingly demonstrated that polyphenols are capable of suppressing experimentally induced inflammation [ 11 , 12 , 16 , 17 , 46 ]. Thus, we hypothesized that RES supplementation also exerts beneficial effects on the intestine by alleviating the DON-induced intestinal inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported that DON can induce inflammation in vivo and in vitro [ 9 , 11 , 30 , 38 ]. Meanwhile, a large number of studies with either porcine intestinal epithelial cell culture or experimental pig models of inflammation have convincingly demonstrated that polyphenols are capable of suppressing experimentally induced inflammation [ 11 , 12 , 16 , 17 , 46 ]. Thus, we hypothesized that RES supplementation also exerts beneficial effects on the intestine by alleviating the DON-induced intestinal inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the composition of the intestinal microbiota affect animal health, such that we can improve animal health by changing the composition of their intestinal microbiota. For example, adding Holly polyphenols in pigs diet alleviated LPS-triggered intestinal injury by altering microbiota composition while reducing intestinal inflammation (87). In the human intestine, Firmicutes and Bacteroidetes are dominant, while Proteobacteria, Actinobacteria, Clostridia etc.…”
Section: Discussionmentioning
confidence: 99%
“…Encouragingly, a holly extract rich in polyphenols and tannins has been shown to alleviate gastrointestinal inflammation in LPS challenged weaned piglets with reduced IL-6 and TNF-α concentrations being reported [38]. Furthermore, holly supplemented diets altered intestinal microbiota in LPS challenged weaned piglets and improved their intestinal barrier function with upregulation of tight junction proteins such as claudin-1 and occludin observed [38]. These results were seen in response to an inclusion of a commercial holly polyphenol product containing 65.5% total polyphenols.…”
Section: Discussionmentioning
confidence: 99%